1994
DOI: 10.1128/mcb.14.8.5425
|View full text |Cite
|
Sign up to set email alerts
|

The cytoplasm of Xenopus oocytes contains a factor that protects double-stranded RNA from adenosine-to-inosine modification.

Abstract: Here we describe studies of double-stranded RNA (dsRNA) adenosine deaminase in Xenopus laevis, in particular during meiotic maturation, the period during which a stage VI oocyte matures to an egg. We show that dsRNA adenosine deaminase is in the nuclei of stage VI oocytes. Most importantly, we demonstrate that the cytoplasm of stage VI oocytes contains a factor that protects microinjected dsRNA from deamination when dsRNA adenosine deaminase is released from the nucleus during meiotic maturation. Our data sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 27 publications
(19 reference statements)
3
23
0
Order By: Relevance
“…Using three different assays we observed that the majority of bFGF mature mRNA was not deaminated in Xenopus stage VI oocytes+ We also found that the bFGF mRNA population isolated after oocyte maturation remained predominantly unmodified, despite its exposure to the ADAR released into the cytoplasm following GVBD+ The latter observation agrees with our earlier report that predicted that the factor cyto-dsRBP would protect cytoplasmically located dsRNA from deamination (Saccomanno & Bass, 1994)+ With all three assays we detected A-to-G transitions in a small fraction of the bFGF mRNA, whether the RNA was isolated from stage FIGURE 4. Restriction-enzyme assays of mixed cDNA populations+ A PhosphorImager image of restriction digests electrophoresed on a 1% agarose gel is shown+ A and B are two independent experiments+ bFGF RNA was amplified by RT-PCR using RNA isolated from either oocytes (lanes 1 and 2) or from matured oocytes (lanes 3 and 4)+ The 900-base-pair PCR products, corresponding to the sense strand of the overlap region, were incubated in the absence (Ϫ) or presence (ϩ) of restriction enzymes (DraIII, ApaI, StuI, and BpmI)+ The percent product digested was obtained by subtracting a background value obtained in the absence of restriction enzymes (Ϫ)+ Background values ranged from 0+6% to a maximum of 1+4%+ The percent digestion was determined with a Molecular Dynamics PhosphorImager using ImageQuaNT software+ VI oocytes or matured oocytes; this suggested that at least a small fraction of the bFGF mRNA from both stages was deaminated by ADAR+ Since ADAR activity is located in the nucleus in stage VI oocytes, our observation of a low level of deaminated bFGF mRNA at this stage indicates that a fraction of the bFGF sense and antisense RNAs are hybridized in the nucleus and acted on by ADARs+ As shown at the top of Figure 1, the bFGF premRNA transcripts can form a much longer duplex prior to splicing that might serve as an ADAR substrate in the nucleus+ However, we did not find any A-to-G changes in the sequence outside the region of complementarity between the mature RNAs, suggesting adenosine deamination occurred on the mature, spliced mRNA, rather than the pre-mRNA (see Fig+ 2 legend)+ Of course, further analysis will be required to prove this definitively+ Within the sensitivity limits of our experiments, the percentage of deaminated bFGF RNA molecules observed before and after oocyte maturation was similar+ We speculate that the small percentage of deaminated bFGF RNA molecules detected after oocyte maturation were deaminated in the oocyte nucleus and persisted after maturation+ However, previous studies indicate that a significant population of the bFGF sense and antisense mRNAs are hybridized in the oocyte cytoplasm (Kimelman & Kirschner, 1989)+ Therefore, we cannot rule out the possibility that a low level of cytoplasmically located bFGF duplex molecules escape protection from cyto-dsRBP and are deaminated by ADAR released at oocyte maturation+ In previous studies hypermutated bFGF RNA transcripts were not observed in the RNA isolated from stage IV or stage VI oocytes, or mixed oocyte populations from total ovary (Kimelman & Kirschner, 1989)+ However, our current data indicate that the percentage of deaminated bFGF transcripts in the RNA population from stage VI oocytes is low, and suggest that analysis of many cDNA clones would be required to identify those which are deaminated+ We believe that we identified deaminated cDNA clones derived from the stage VI oocyte RNA because we analyzed large populations of cDNA molecules utilizing three different methods+…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Using three different assays we observed that the majority of bFGF mature mRNA was not deaminated in Xenopus stage VI oocytes+ We also found that the bFGF mRNA population isolated after oocyte maturation remained predominantly unmodified, despite its exposure to the ADAR released into the cytoplasm following GVBD+ The latter observation agrees with our earlier report that predicted that the factor cyto-dsRBP would protect cytoplasmically located dsRNA from deamination (Saccomanno & Bass, 1994)+ With all three assays we detected A-to-G transitions in a small fraction of the bFGF mRNA, whether the RNA was isolated from stage FIGURE 4. Restriction-enzyme assays of mixed cDNA populations+ A PhosphorImager image of restriction digests electrophoresed on a 1% agarose gel is shown+ A and B are two independent experiments+ bFGF RNA was amplified by RT-PCR using RNA isolated from either oocytes (lanes 1 and 2) or from matured oocytes (lanes 3 and 4)+ The 900-base-pair PCR products, corresponding to the sense strand of the overlap region, were incubated in the absence (Ϫ) or presence (ϩ) of restriction enzymes (DraIII, ApaI, StuI, and BpmI)+ The percent product digested was obtained by subtracting a background value obtained in the absence of restriction enzymes (Ϫ)+ Background values ranged from 0+6% to a maximum of 1+4%+ The percent digestion was determined with a Molecular Dynamics PhosphorImager using ImageQuaNT software+ VI oocytes or matured oocytes; this suggested that at least a small fraction of the bFGF mRNA from both stages was deaminated by ADAR+ Since ADAR activity is located in the nucleus in stage VI oocytes, our observation of a low level of deaminated bFGF mRNA at this stage indicates that a fraction of the bFGF sense and antisense RNAs are hybridized in the nucleus and acted on by ADARs+ As shown at the top of Figure 1, the bFGF premRNA transcripts can form a much longer duplex prior to splicing that might serve as an ADAR substrate in the nucleus+ However, we did not find any A-to-G changes in the sequence outside the region of complementarity between the mature RNAs, suggesting adenosine deamination occurred on the mature, spliced mRNA, rather than the pre-mRNA (see Fig+ 2 legend)+ Of course, further analysis will be required to prove this definitively+ Within the sensitivity limits of our experiments, the percentage of deaminated bFGF RNA molecules observed before and after oocyte maturation was similar+ We speculate that the small percentage of deaminated bFGF RNA molecules detected after oocyte maturation were deaminated in the oocyte nucleus and persisted after maturation+ However, previous studies indicate that a significant population of the bFGF sense and antisense mRNAs are hybridized in the oocyte cytoplasm (Kimelman & Kirschner, 1989)+ Therefore, we cannot rule out the possibility that a low level of cytoplasmically located bFGF duplex molecules escape protection from cyto-dsRBP and are deaminated by ADAR released at oocyte maturation+ In previous studies hypermutated bFGF RNA transcripts were not observed in the RNA isolated from stage IV or stage VI oocytes, or mixed oocyte populations from total ovary (Kimelman & Kirschner, 1989)+ However, our current data indicate that the percentage of deaminated bFGF transcripts in the RNA population from stage VI oocytes is low, and suggest that analysis of many cDNA clones would be required to identify those which are deaminated+ We believe that we identified deaminated cDNA clones derived from the stage VI oocyte RNA because we analyzed large populations of cDNA molecules utilizing three different methods+…”
Section: Discussionsupporting
confidence: 87%
“…One study suggests that a region of complementarity between the sense and antisense transcripts from the basic fibroblast growth factor (bFGF) gene are hypermutated according to the above scenario (Kimelman & Kirschner, 1989)+ In X. laevis the bFGF gene is transcribed bidirectionally to produce a 4+2-kb sense transcript and a 1+35-kb antisense transcript (Kimelman et al+, 1988;Volk et al+, 1989)+ A 900-base-pair overlap region exists between the mature sense and antisense transcripts, at each of their 39 ends (see Fig+ 1)+ Previously it was reported that, although the bFGF duplex was not deaminated in stage VI oocytes, it became deaminated after oocyte maturation, and was subsequently degraded (Kimelman & Kirschner, 1989)+ This report was consistent with our observation that ADAR activity is located in the nucleus in stage VI oocytes, and is released into the cytoplasm during oocyte maturation, when the nuclear membrane breaks down (germinal vesicle breakdown (GVBD); Saccomanno & Bass, 1994)+ That is, assuming the majority of the bFGF duplex is cytoplasmic, it should not be exposed to ADAR activity until after GVBD+ However, further analysis of ADAR activity in our laboratory identified a factor(s) in the cytoplasm of stage VI oocytes, cytoplasmic dsRNA binding protein (cyto-dsRBP), that specifically protects dsRNA from ADAR activity released at oocyte maturation (Saccomanno & Bass, 1994) + Although this factor was characterized by microinjection of an exogenous dsRNA, the presence of cyto-dsRBP was in conflict with the apparent deamination of endogenous bFGF RNA (Kimelman & Kirschner, 1989) and suggested the bFGF duplex should be protected from adenosine deamination in the stage VI oocyte and throughout oocyte maturation+ Discussions between the two laboratories provided a possible solution to the apparent conflicts+ In particular, although many laboratories induce maturation in vitro by incubating oocytes with progesterone, the protocols used by Kimelman and Kirschner involved microinjecting a crude preparation of maturation promoting factor (MPF) into stage VI oocytes+ Experiments in our laboratory demonstrated that the crude preparation of MPF contained a significant concentration of ADAR activity (M+ Paul & B+ Bass, unpubl+ data)+ Possibly, the injection of exogenous ADAR into the cytoplasm displaced the cyto-dsRBP bound to the bFGF duplex, leading to its aberrant deamination+ Nonetheless, since ADARs require base-paired substrates, the work by Kimelman and Kirschner indicates that the bFGF sense and antisense RNAs are hybridized in the cytoplasm of stage VI oocytes+…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Indeed, the presence of inhibitors of DRADA in the form of nonsequence-specific dsRNA binding proteins has been reported in Xenopus oocytes and also in silk moth embryos. These inhibitors may regulate the action of DRADA developmentally by suhcellular compartmentalization (Skeiky and Iatrou, 1991;Saccomanno and Bass, 1994). Alternatively, this negative regulator could be a dsRNA for which DRADA enzymes have a similar affinity as f'or GluR RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, A→I RNA editing of repeat RNAs occurs only at low levels in ovaries and testes 8 . Furthermore, the nuclear versus cytoplasmic localization and activation of ADARs are regulated during maturation of oocytes and early embryos of X. laevis 93 .…”
Section: Suppression Of Rasirna?mentioning
confidence: 99%